Effect of Vasicine on Kidney Histomorphology in Streptozotocin-Induced Diabetic Wistar Rats - Sai Subhadra Ravali Kompella; Usha Kumary Santha; Thandavan Arthanari Kannan; Kalaiselvi Lakshmanan; Sridevi Ponnada (Majalah Biomorfologi)
Highlights 1. Justicia adhatoda leaves can be used as herbal medicine to treat diabetes and its associated conditions. 2. Vasicine in Justicia leaves helps protect kidney health in individuals with diabetes.